Endovascular treatment in older adults with acute ischemic stroke in the MR CLEAN Registry. (14th July 2020) - Groot, Adrien E.; Treurniet, Kilian M.; Jansen, Ivo G.H.; Lingsma, Hester F.; Hinsenveld, Wouter; van de Graaf, Rob A.; Roozenbeek, Bob; Willems, Hanna C.; Schonewille, Wouter J.; Marquering, Henk A.; van den Berg, René; Dippel, Diederik W.J.; et al.
Abstract : Objective: To explore clinical outcomes in older adults with acute ischemic stroke treated with endovascular thrombectomy (EVT). Methods: We included consecutive patients (2014–2016) with an anterior circulation occlusion undergoing EVT from the Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands (MR CLEAN) Registry. We assessed the effect of age (dichotomized at ≥80 years and as continuous variable) on the modified Rankin Scale (mRS) score at 90 days, symptomatic intracranial hemorrhage (sICH), and reperfusion rate. The association between age and mRS was assessed with multivariable ordinal logistic regression, and a multiplicative interaction term was added to the model to assess modification of reperfusion by age on outcome. Results: Of the 1, 526 patients, 380 (25%) were ≥80 years of age (referred to here as older adults). Older adults had a worse functional outcome than younger patients (adjusted common odds ratio [acOR] for an mRS score shift toward better outcome 0.31, 95% confidence interval [CI] 0.24–0.39). Mortality was also higher in older adults (51% vs 22%, adjusted odds ratio 3.12, 95% CI 2.33–4.19). There were no differences in proportion of patients with mRS scores of 4 to 5, sICH, or reperfusion rates. Successful reperfusion was more strongly associated with a shift toward good functional outcome in older adults than in younger patients (acOR 3.22, 95% CI 2.04–5.10 vs 2.00, 95% CI 1.56–2.57, p interaction = 0.026). Conclusion: Older age is associated with an increased absolute risk of poor clinical outcome, while the relative benefit of successful reperfusion seems to be higher in these patients. These results should be taken into consideration in the selection of older adults for EVT.